2023
DOI: 10.3390/vaccines11071196
|View full text |Cite
|
Sign up to set email alerts
|

Booster Immunization Improves Memory B Cell Responses in Older Adults Unresponsive to Primary SARS-CoV-2 Immunization

Marije K. Verheul,
Kim H. Nijhof,
Mary-lène de Zeeuw-Brouwer
et al.

Abstract: The generation of a specific long-term immune response to SARS-CoV-2 is considered important for protection against COVID-19 infection and disease. Memory B cells, responsible for the generation of antibody-producing plasmablasts upon a new antigen encounter, play an important role in this process. Therefore, the induction of memory B cell responses after primary and booster SARS-CoV-2 immunizations was investigated in the general population with an emphasis on older adults. Participants, 20–99 years of age, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…Part of the antibody data measured for 12–17-year-old participants has previously been published in a study showing that the antibody levels in younger individuals are generally higher, compared to those in (older) adults ( 12 ). Interestingly, the numbers of memory B cells in children are lower compared to those we previously determined in adults (18-50 years of age) after two vaccine doses without a previous infection ( 18 ) (median = 1.25/1*10 5 PBMC for children (n = 7) and 10.5/1*10 5 PBMC for adults (n = 32). This potentially indicates that B cells in children are more likely to become antibody-producing plasmablasts after COVID-19 mRNA vaccination, while B cells in adults may be more likely to differentiate into memory B cells.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Part of the antibody data measured for 12–17-year-old participants has previously been published in a study showing that the antibody levels in younger individuals are generally higher, compared to those in (older) adults ( 12 ). Interestingly, the numbers of memory B cells in children are lower compared to those we previously determined in adults (18-50 years of age) after two vaccine doses without a previous infection ( 18 ) (median = 1.25/1*10 5 PBMC for children (n = 7) and 10.5/1*10 5 PBMC for adults (n = 32). This potentially indicates that B cells in children are more likely to become antibody-producing plasmablasts after COVID-19 mRNA vaccination, while B cells in adults may be more likely to differentiate into memory B cells.…”
Section: Discussioncontrasting
confidence: 71%
“…Once received by the laboratory at the National Institute for Public Health and the Environment (RIVM), the Netherlands, serum from microtubes and from blood sample tubes were spun down and frozen at -80°C as previously described ( 12 ). Heparin tubes were used to collect PBMCs (subgroup only), which were isolated with Lymphoprep as described previously ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large national cohort study [ 20 ] assessed age-specific estimates of the risk of severe outcomes for Omicron relative to Delta, and reported that the adjusted hazard ratio of death was approximately three times higher for unvaccinated patients aged at least 80 years compared with those aged 30–39. A recent study [ 21 ] reported that older people tended to have lower frequencies of specific memory B cell responses after the primary vaccination series than younger people, but that the booster vaccination produced a great increase in the frequencies of memory B cells for older people with low frequencies after the primary series. These previous studies [ 19 21 ] support our findings that among older people aged 80 and older, it is more difficult to reduce the risk of severe COVID-19, but that booster vaccination is more effective, compared to younger people.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 21 ] reported that older people tended to have lower frequencies of specific memory B cell responses after the primary vaccination series than younger people, but that the booster vaccination produced a great increase in the frequencies of memory B cells for older people with low frequencies after the primary series. These previous studies [ 19 21 ] support our findings that among older people aged 80 and older, it is more difficult to reduce the risk of severe COVID-19, but that booster vaccination is more effective, compared to younger people.…”
Section: Discussionmentioning
confidence: 99%